Generalist Therapy Intervention For A Schizoaffective Patient With Auditory Hallucinations: A Case Report - Fauzania, Syifa Nurul; Hendrawati, Hendrawati; Amira, Iceu (Utami Publisher, 2025)
Schizoaffective disorder often leads to disturbances in the patient's perception and sense of reality. Hallucination is one of the main symptoms of psychotic disorders and is also found in schizoaffective disorder. If not properly managed, hallucinations can lead to a lack of self-control, potentially causing harm to oneself and their surroundings. Hallucination disturbances can be managed through generalist therapy, including recognizing hallucinations and using techniques such as rebuking, talking, taking medication, and engaging in positive activities. The purpose of this case report is to describe the implementation of generalist therapy in a schizoaffective patient with sensory perception disturbance: auditory hallucinations. This study used a case report method with a single case described descriptively, following the nursing care approach. Data were collected through observation, interviews, and physical examinations. The intervention was the application of generalist therapy conducted over five days. The evaluation results showed that the client was able to recognize and control the hallucinations. Generalist therapy for hallucinations can assist patients in recognizing and managing their symptoms. It is expected that healthcare professionals will routinely implement generalist therapy to help reduce hallucination symptoms in patients.